2015
DOI: 10.1103/physrevlett.115.246402
|View full text |Cite|
|
Sign up to set email alerts
|

Pressure-Induced Mott Transition Followed by a 24-K Superconducting Phase inBaFe2S3

Abstract: We performed high-pressure study for a Mott insulator BaFe_{2}S_{3}, by measuring dc resistivity and ac susceptibility up to 15 GPa. We found that the antiferromagnetic insulating state at the ambient pressure is transformed into a metallic state at the critical pressure, P_{c}=10  GPa, and the superconductivity with the optimum T_{c}=24  K emerges above P_{c}. Furthermore, we found that the metal-insulator transition (Mott transition) boundary terminates at a critical point around 10 GPa and 75 K. The obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 26 publications
4
75
2
Order By: Relevance
“…This increase in T N is consistent with muon spin relaxation experiments conducted in the low pressure region [11]. Yamauchi et al conducted dc resistivity measurements and observed a maximum in T N at ∼ 3 GPa followed by a monotonic reduction with increasing pressure [6]. Reasons for the discrepancy could be anisotropies in the resistivity or slightly different stochiometries [25].…”
supporting
confidence: 79%
See 1 more Smart Citation
“…This increase in T N is consistent with muon spin relaxation experiments conducted in the low pressure region [11]. Yamauchi et al conducted dc resistivity measurements and observed a maximum in T N at ∼ 3 GPa followed by a monotonic reduction with increasing pressure [6]. Reasons for the discrepancy could be anisotropies in the resistivity or slightly different stochiometries [25].…”
supporting
confidence: 79%
“…It was found that nesting can be excluded as a mechanism for the AFM order, in contrast to the FeAs-based compounds [9]. At the critical pressure p c ∼ 10 GPa an insulator-metal transition occurs and a non-magnetic SC phase with transition temperatures up to 24 K at 12 -13 GPa was observed [5,6].…”
mentioning
confidence: 99%
“…To stabilize an orbital selective Mott phase we may introduce a hole or electron doping to the system. As it was shown for a two orbital system with nonzero Hund's coupling and crystal field splitting (Werner & Millis 2007), for a range of doping values, the charge is incorporated to one of the orbitals making it metallic while the other remain insulating. This behavior is also observed for a three orbital system as it is shown in Fig.…”
Section: Doped Systemmentioning
confidence: 91%
“…These results indicate that the Ni doping has more influence on the electrical property than the magnetic property of BaFe 2 Se 3 . In BaFe 2 S 3 , the insulating behavior at ambient pressure is gradually suppressed with increasing pressure and superconductivity is induced near 10 GPa, where electrical resistivity shows a metallic behavior [8,9]. The correlation between superconductivity and an insulator-metal transition in BaFe 2 S 3 suggests that the Ni-doped Ba(Fe 1-x Ni x ) 2 Se 3 may become superconducting by applying sufficient pressure or chemical substitution to induce the insulator-metal transition.…”
Section: Synthesis Of Thementioning
confidence: 99%
“…A possibility of superconductivity in BaFe 2 Se 3 was suggested by doping or application of pressure because they may decrease the band gap of BaFe 2 Se 3 [3,7]. Very recently a pressure-induced superconductivity has been reported in BaFe 2 S 3 under high pressure of ~ 10 GPa [8,9]. However, superconductivity in MFe 2 Se 3 (M = K, Ba, and Cs) is still not revealed by doping or application of pressure [3,10].…”
Section: Introductionmentioning
confidence: 99%